Nucleation Kinetics, Growth and Characterization Studies of a Diamagnetic Crystal-Zinc Sulphate Heptahydrate (ZSHH) - R. Kanagadurai; R. Durairajan; R. Sankar; G. Sivanesan; S. P. Elangovan; R. Jayavel (E-Journal of Chemistry)
Solubility, metastable zone width and induction period measurements have been performed on zinc sulphate heptahydrate (ZSHH). Interfacial tension values determined from induction period measurements have been used for the evaluation of the nucleation parameters such as radius of critical nucleus and the free energy of formation of critical nucleus. ZSHH crystallizes in the orthorhombic structure. Crystals of diamagnetic zinc sulphate heptahydrate have been grown by temperature lowering solution growth technique with the optimized growth parameters. The as-grown ZSHH crystals were characterized by the powder X-ray diffraction, UV-VIS absorption and transmittance, FT-IR absorption, TG-DTA, microhardness and etching studies.